Pemanfaatan Facebook Pro sebagai Platform Promosi Produk UMKM - Saputra, Imam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face significant challenges in product marketing, particularly in the digital era. Many MSME owners have not fully utilized digital technologies to expand their market reach and enhance product sales. One platform that can be leveraged is Facebook Pro, which allows MSMEs to promote products affordably and with broad reach. This study aims to provide training to MSME owners in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency, on how to utilize Facebook Pro as a digital marketing tool. The training, held on October 26, 2024, involved 30 participants from various MSME sectors. The training covered basic digital marketing concepts, creating business accounts, managing business pages, creating paid advertising campaigns, and using analytical tools to evaluate ad performance. The results showed a significant increase in participants’ understanding of digital marketing, with pre-test and post-test scores improving by an average of 30%. Most participants successfully applied the knowledge gained by running ad campaigns using Facebook Pro. Although challenges related to ad budget management and adaptation to Facebook’s algorithm changes were encountered, the solutions provided during the training helped participants overcome these issues. This activity is expected to assist MSMEs in becoming more independent in digital marketing and to enhance their competitiveness.